Genomic Analysis of Delftia tsuruhatensis Strain TR1180 Isolated From A Patient From China With In4-Like Integron-Associated Antimicrobial Resistance - Cheng, Cong; Zhou, Wangxiao; Dong, Xu; Zhang, Peiyao; Zhou, Kexin; Zhou, Danying; Qian, Changrui; Lin, Xi; Li, Peizhen; Li, Kewei; Bao, Qiyu; Xu, Teng; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Delftia tsuruhatensis has become an emerging pathogen in humans. There is scant information on the genomic characteristics of this microorganism. In this study, we determined the complete genome sequence of a clinical D. tsuruhatensis strain, TR1180, isolated from a sputum specimen of a female patient in China in 2019. Phylogenetic and average nucleotide identity analysis demonstrated that TR1180 is a member of D. tsuruhatensis. TR1180 exhibited resistance to β-lactam, aminoglycoside, tetracycline and sulphonamide antibiotics, but was susceptible to phenicols, fluoroquinolones and macrolides. Its genome is a single, circular chromosome measuring 6,711,018 bp in size. Whole-genome analysis identified 17 antibiotic resistance-related genes, which match the antimicrobial susceptibility profile of this strain, as well as 24 potential virulence factors and a number of metal resistance genes. Our data showed that Delftia possessed an open pan-genome and the genes in the core genome contributed to the pathogenicity and resistance of Delftia strains. Comparative genomics analysis of TR1180 with other publicly available genomes of Delftia showed diverse genomic features among these strains. D. tsuruhatensis TR1180 harbored a unique 38-kb genomic island flanked by a pair of 29-bp direct repeats with the insertion of a novel In4-like integron containing most of the specific antibiotic resistance genes within the genome. This study reports the findings of a fully sequenced genome from clinical D. tsuruhatensis, which provide researchers and clinicians with valuable insights into this uncommon species.